2021
DOI: 10.1002/prep.202100022
|View full text |Cite
|
Sign up to set email alerts
|

Thermally‐Driven Changes to Porosity in TATB‐Based High Explosives

Abstract: Ultra‐small‐ and small‐angle neutron scattering techniques were employed to quantify thermally driven changes to the microstructure of the TATB‐based composite high explosive, PBX 9502. Samples of PBX 9502 were studied in‐situ at temperatures ranging from 25 to 220 °C and after re‐equilibration at ambient temperature. Significant changes to the void size and morphology within the PBX 9502 microstructure were observed upon heating and are consistent with the known increase in the shock sensitivity of thermally‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The gas volume fraction shown in Figure 7(c,d) is continuous in both the impermeable and permeable explosive layers. The gas volume fraction is similar in magnitude to the gas volume fraction reported in [14].…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The gas volume fraction shown in Figure 7(c,d) is continuous in both the impermeable and permeable explosive layers. The gas volume fraction is similar in magnitude to the gas volume fraction reported in [14].…”
Section: Resultssupporting
confidence: 80%
“…The gas volume frac- [7]. Predicted solid fraction at various times using the model in [14] coupled to the MMP model. tion shown in Figure 7(c,d) is continuous in both the impermeable and permeable explosive layers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…micron-sized) pores. Armstrong and Mang (2021) performed a similar study by small-angle neutron scattering on PBX 9502, and showed that micron-sized pores grow until 120 • C, and that new pores appear above this temperature. They found, additionally, some residual growth after cooling back to ambient.…”
Section: Introductionmentioning
confidence: 96%